LYMPHOCYTIC HYPOPHYSITIS; A RARE AUTOIMMUNE DISORDER THAT PRESENT AS LARGE SELLAR SUPRA SELLAR MASS WITH COMPLETE RESOLUTION WITH STEROIDS - Rafiq, Mirza Faisal Ahmed; Farooq, Umar; Khan, Adil Aziz; Ain, Noor ul (Journal of Ayub Medical College Abbottabad, 2015)
Significant proportion of sellar masses is seen in clinical practice. They range from most common pituitary adenomas to rare inflammatory lesions. Presentation can vary and depends if it secretes any hormone or imparts a pressure effect upon the surrounding vital structures. Radiological imaging coupled with histopathology is important tools of diagnosis. Management options depend upon type of disease. Keywords: Lymphocytic hypophisitis, autoimmune, pituitary, sellar mass, steroids